2018
DOI: 10.20944/preprints201804.0382.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermal Conductivity of an AZ31 Sheet After Accumulative Roll Bonding

Abstract: Accumulative roll bonding (ARB) is one of methods of severe plastic deformation which is relevant for industrial production of sheets. While mechanical properties of several magnesium alloys subjected to ARB process have been studied, the physical properties have been reported only for some magnesium alloys. These properties are influenced by the texture developed during the ARB process and the temperature load. In the presented contribution, we studied thermal diffusivity and thermal conductivity of an AZ31 m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…It is usually due to the texture developed in the deformed materials and anisotropy of the hexagonal Mg cell. The anisotropy can be manifested not only in mechanical properties but also in other physical properties such as thermal expansion, thermal conductivity, or internal friction . The microstructure and mechanical properties of pure magnesium submitted to RSW were studied by Gan et al They observed a refined inhomogeneous microstructure which varied from the center to surface of the samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is usually due to the texture developed in the deformed materials and anisotropy of the hexagonal Mg cell. The anisotropy can be manifested not only in mechanical properties but also in other physical properties such as thermal expansion, thermal conductivity, or internal friction . The microstructure and mechanical properties of pure magnesium submitted to RSW were studied by Gan et al They observed a refined inhomogeneous microstructure which varied from the center to surface of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropy can be manifested not only in mechanical properties [4][5][6][7] but also in other physical properties such as thermal expansion, [8] thermal conductivity, [9] or internal friction. [10] The microstructure and mechanical properties of pure magnesium submitted to RSW were studied by Gan et al [11] They observed a refined inhomogeneous microstructure which varied from the center to surface of the samples. Nevertheless, the yield stress and ultimate tensile strength increased, with a tendency to saturate, with increased amount of RSW deformation.…”
Section: Introductionmentioning
confidence: 99%